Smoothed particle hydrodynamics study of friction of the coarse-grained α-Al2O3/α-Al2O3 and α-Fe2O3/α-Fe2O3 contacts in behavior of the spring interfacial potential. (July 2019) - Van Sang, Le; Yano, Akihiko; Isohashi, Ai; Sugimura, Natsuko; Washizu, Hitoshi
Abstract: The paper investigates sliding friction of the α-Al2 O3 /α-Al2 O3 and α-Fe2 O3 /α-Fe2 O3 contacts by using the spring interfacial potential. It is found that at micronscale the friction properties of the oxides are almost independent of the coarse-graining and are the same in the different sliding directions. Even the hardness contacts friction coefficient shows a decrease with increasing intensity of the normal component of the interfacial interaction force. This result is as an implementation for the previous observations of sliding friction of various materials that showed that a drop of friction coefficient with increasing externally applied normal load has originated from deformation of interfaces or occurrence of debris at contact, indicating an unsteady contact. Highlights: At micron-scale, friction of these systems is independent of the sliding directions. Friction strongly depends on the modeled interfacial force. The coarse-graining does not result in the observed friction properties.